2014
DOI: 10.1055/s-0034-1391078
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of endoscopic submucosal dissection of rectal tumors extending to the dentate line

Abstract: ESD for RTDLs demonstrated safety and effectiveness comparable to ESD in proximal rectal lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(73 citation statements)
references
References 8 publications
4
69
0
Order By: Relevance
“…There are a few reports on use of gastric ESD in children[7-9]. Further, there are a couple of reports showing that ESD is useful for treating anorectal tumors close to the dentate line[10,11]. This procedure is an attractive option for en bloc resection of large sessile or flat colorectal lesions and is associated with very low recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few reports on use of gastric ESD in children[7-9]. Further, there are a couple of reports showing that ESD is useful for treating anorectal tumors close to the dentate line[10,11]. This procedure is an attractive option for en bloc resection of large sessile or flat colorectal lesions and is associated with very low recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, ESD increased in Period B compared with Period A. Moreover, Imai et al [26] demonstrated the feasibility of ESD for rectal tumor extending to the dentate line. In our study, 82.4 % of locally recurrent patients in Period A and two of all [12] reported that salvage surgery might be effectiveprimarly in patients with T1 tumors despite the high risk of local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Cases at the dental line are recently reported to be difficult for ESD (26) because there are lots of vessels at the location. However, we manage thick vessels during ESD with the scissor-type knife (Clutch cutter).…”
Section: Difficult Factors Of Colorectal Esdmentioning
confidence: 99%